SEJARAH, KEDUDUKAN, SERTA PROSPEK PERANGKAT DESA DI INDONESIA - Sadu Wasistiono (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
Position of village government apparatus in Indonesia is still ambivalent until now, because of unclear village institution position. Law Nomor 6 Year 2014 about Village have the hybrid model, combination between self governing community and local self government (but quasi). According to Indonesia Constitution 1945 (before amendment), village or the other names will be construct as local government, and implemented in several law about local government during 1945-1979. After amendment, village or the other names, will construct as social community. Facing rapid change of industrial revolution 4.0 (Schwab; 2016) and society 5.0 (Fukuyama; 2018), Indonesia government should choose one of three choices namely : self governing community, local self government, and hybrid. Key words : ambivalence of village apparatus position, self governing community, local self government, hybrid.